Community survey on the knowledge, attitude, and practice of blood donation in Ebonyi State, Southeast Nigeria - Nnachi, Oluomachi C.; Akpa, Chinedu O.; Onwe, Ogah E.; Nwani, Emmanuel I.; Nwani, Favour O.; Ekpagu, Victor; Onoh, Toochukwu J. (International Journal Of Community Medicine And Public Health, 2022)
Background: Blood transfusion is a vital component of health care delivery. The populace perspective on blood donation is critical to ensure adequate and safe blood supply. This study aimed to assess the knowledge, attitude, and practice of blood donation among adults in a southeastern state in Nigeria. Methods: This was a community-based cross-sectional study. A total of 636 participants aged 18-60 years participated in the study. Multi-stage and systematic random sampling was involved in selection of study participants and pretested questionnaires were administered. Fishers exact test was used to test statistical significance and multivariate logistic regression was used to determine the predictors of outcome and control of confounding variables. Results: Majority, 71.2% of the participants were assessed as having good knowledge while 62.9% had a good attitude towards blood donation but only 32.5% had good practice. Most of the reasons for not donating blood include that no one asked for it (42.3%) and didn’t think of it (24.7%). Males, higher education level, and being an orthodox church member were positively associated with good blood donation attitude. Conclusions: Knowledge and attitude towards blood donation is good. However, the level of practice is low. The most important reasons for not donating blood include lack of information on when it is needed and self-perceived risks of pain, anemia, and unfitness due to manual/farm work. Community education on the safety of blood donation practices and establishment of donor reminder systems are needed to improve blood donation practices.